THE CORRELATION BETWEEN STUDENTS’ INTEREST IN SPEAKING AND THEIR SPEAKING ACHIEVEMENT - Serawati, Sri; Supardi, Iwan; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study was aimed to find out the correlation between students? interest in speaking and their speaking achievement at MAN 2 Filial Pontianak. There was two problems that need to be discussed in this research, first was how strong the correlation between students? interest in speaking and their speaking achievement. Second, how much was the contribution of students? interest through their speaking achievement. The researcher used purposive sampling technique to choose the sample. There were 21 students of the eleventh grade. Class B was chosen as the sample of this research. The instruments of this research were questionnaire and speaking score rubric. The researcher used Pearson product moment to calculate the data of students? interest and speaking achievement. The result showed that there was significant or positive correlation and indicating a medium correlation. The contribution of students? interest through their speaking achievement was in the amount of 35.6%. Therefore, this data was answered the research question of this research. Keyword: Correlation, Students? Interest, Speaking Achievement